PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 023 SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study originated from low IPA students learning outcomes, withan average value of 63.35 class. While the value of minimum completenesscriteria (KKM) IPA 65. This research is a classroom action research (CAR).Conducted aiming to improve science learning outcomes fourth grade students ofSDN 023 Segajah River Kubu district of Rokan Hilir. Formulation of the problem:Is the application of problem-based learning model to improve learning outcomesIPA 023 fourth grade students of SDN Segajah River Kubu district of Rokan Hilir.Data were collected through observation using the observation sheet for learningoutcomes through UH UH I and II. As for the improvement of learning outcomesthat occurred before the individual TOD 9 students (45%) were completed with anaverage of 63.35. While on one cycle after PTK individually 16 students (80%)were completed with an average of 75, while the two cycles were completedsebayak 18 people or 90% with an average of 80 So the thoroughness ofimproving student learning outcomes of the score kesiklus basis of the increase of11.65% from the base score kesiklus while two increased to 16.65%. While theactivities of students in the first cycle with an average of 65% in the second cyclean average of 82.5%. While the activity of the teacher on the first cycle with anaverage of 60% in the second cycle reaches 77.5%. These results prove that theapplication of problem-based learning model to improve learning outcomes IPA023 fourth grade students of SDN Segajah River Kubu district Rokan Hilir.Keywords: Problem-based learning, science learning outcomes